PENGARUH UKURAN PERUSAHAAN, AUDIT LAG, DAN FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN - FAJAR SANTOSO, BUDI; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2018)
Going concern problem of the company which results in the companys doubt in maintaining the continuity of its business in the future. This makes the need for research that aims to determine the effect of firm size, audit lag, and financial distress on going-concern audit opinion on the infrastructure, utility, and transportation sector companies registered in the Indonesian Stock Exchange (IDX) in 2012 to 2016. Samples in this study are the infrastructure, utilities, and transportation sector companies registered (BEI) in 2012 to 2016 using proposive sampling obtained 175 companies that match the sampling criteria. Research carried out using logistic regression data analysis techniques with SPSS 23 test equipment which obtained the results of the research firm size variable negatively affected the going concern audit opinion, audit lag and financial distress variables not affect to going concern audit opinion Keywords:Going-Concern Audit Opinion, Firm Size, Audit Lag,and Financial Distress